Xer Site Specific Recombination: Double and Single Recombinase Systems - Castillo, Fabio; Benmohamed, Amal; Szatmari, George (Frontiers in Microbiology, 2017)
The separation and segregation of newly replicated bacterial chromosomes can be constrained by the formation of circular chromosome dimers caused by crossing over during homologous recombination events. In E. coli and most bacteria, dimers are resolved to monomers by site-specific recombination, a process performed by two Chromosomally Encoded tyrosine Recombinases (XerC and XerD). XerCD recombinases act at a 28 bp recombination site dif, which is located at the replication terminus region of the chromosome. The septal protein FtsK controls the initiation of the dimer resolution reaction, so that recombination occurs at the right time (immediately prior to cell division) and at the right place (cell division septum). XerCD and FtsK have been detected in nearly all sequenced eubacterial genomes including Proteobacteria, Archaea, and Firmicutes. However, in Streptococci and Lactococci, an alternative system has been found, composed of a single recombinase (XerS) genetically linked to an atypical 31 bp recombination site (difSL). A similar recombination system has also been found in ε-proteobacteria such as Campylobacter and Helicobacter, where a single recombinase (XerH) acts at a resolution site called difH. Most Archaea contain a recombinase called XerA that acts on a highly conserved 28 bp sequence dif, which appears to act independently of FtsK. Additionally, several mobile elements have been found to exploit the dif/Xer system to integrate their genomes into the host chromosome in Vibrio cholerae, Neisseria gonorrhoeae and Enterobacter cloacae. This review highlights the versatility of dif/Xer recombinase systems in prokaryotes and summarizes our current understanding of homologs of dif/Xer machineries.